Joint VNF Decomposition and Migration for Cost-Efficient VNF Forwarding Graph Embedding - Afrasiabi, Seyedeh Negar; Ebrahimzadeh, Amin; Azhdari, Azadeh; Mouradian, Carla; Li, Wubin; Szabo, Robert; Glitho, Roch H. (IEEE Global Communications Conference (Online), 2023)
Network Function Virtualization (NFV) enables the decoupling of network functions from dedicated hardware to run them as software instances on commodity servers through virtualization, replacing hardware-based network functions with software-based Virtual Network Functions (VNFs). In this paper, we study the joint problem of VNF decomposition and migration to address VNF embedding in NFV resource allocation (NFV-RA). More specifically, we investigate how VNF migration and VNF decomposition can be mutually beneficial to minimize the embedding cost of network services. After presenting a novel formulation of the problem as an integer linear programming (ILP), we validate it by CPLEX and show that our joint VNF decomposition and migration approach can outperform the VNF decomposition-only approach by 20% in terms of embedding cost.